Mitochondrial dysfunction in cardiovascular disease: Towards exercise regulation of mitochondrial function - Li, Kunzhe; Wan, Bingzhi; Li, Sujuan; Chen, Zhixin; Jia, Hao; Song, Yinping; Zhang, Jiamin; Ju, Wenyu; Ma, Han; Wang, Youhua (Frontiers in Physiology, 2023)
The morbidity and mortality of cardiovascular diseases have been high, in which mitochondrial dysfunction plays a vital role in heart failure, the outcome of cardiac remodeling. In recent years, there has been a growing body of research targeting exercise modulation of mitochondrial dysfunction to improve heart failure. Therefore, finding practical treatment goals and exercise programs to improve cardiovascular disease is critical. With the recent development of exercise drug combination therapies, better treatment options are possible. This review summarizes abnormal mitochondrial function in pathological states and intervention strategies for exercise therapy.